PENGUJIAN KERENTANAN DAN PENETRASI KEAMANAN PADA APLIKASI WEB MANAJEMEN SKRIPSI PRODI XYZ - Listartha, I Made Edy; Saskara, Gede Arna Jude; Santyadiputra, Gede Saindra (Fakultas Teknik, Universitas Tadulako, 2021)
Information systems provide ease in creating transparency and process management. This advantage becomes the basis of department xyz reference to build a web-based information system to manage student thesis, and implement security features on web applications built to prevent exploitation from bad parties. Security system features that have been built to protect applications may still have vulnerabilities. Appropriate methods and techniques are needed in looking at possible vulnerabilities in the components, libraries, and systems underlying the web applications used. The study looked for vulnerabilities with automated and manual techniques by looking for known vulnerabilities based on OWASP 2017 using the Burp Suite app. The vulnerability detection results are then mapped in three levels of danger by looking at the risk of exploitation.